Enhanced magnetization and anisotropy in Mn-Ga thin films grown on LSAT - Karel, Julie; Casoli, Francesca; Nasi, L.; Lupo, P.; Sahoo, R.; Ernst, B.; Markou, Anastasios; Kalache, A.; Cabassi, Riccardo; Albertini, F.; Felser, Claudia (Applied Physics Letters, 2017)
Epitaxial thin films of MnxGa1-x (x = 0.70, 0.74) grown on single crystal (LaAlO3)0.3(Sr2TaAlO6)0.7 [LSAT] substrates exhibit an enhanced magnetic moment and magnetic anisotropy in comparison to films of the same composition grown epitaxially on SrTiO3 [STO] single crystal substrates. Atomic and magnetic force microscopy revealed films exhibiting uniform grains and magnetic domain structures, with only minor differences between the films grown on different substrates. High resolution transmission electron microscopy on the x = 0.74 sample grown on LSAT showed a well-ordered, faceted film structure with the tetragonal c-axis oriented out of the film plane. Further, misfit dislocations, accommodating the lattice mismatch, were evidenced at the film/substrate interface. The out of plane c lattice parameter is larger for all x in the films grown on LSAT, due to the smaller substrate lattice parameter compared to STO. The increase in c generates a larger distortion of the tetragonal lattice which promotes the enhanced magnetization and magnetocrystalline anisotropy. These results indicate that LSAT is a promising substrate for realizing highly tailored magnetic properties for future spintronic applications not only in MnxGa1-x but also in the broader class of tetragonal Mn-Z-Ga (Z = transition metal) materials.
CRIS-Team Scopus Importer:2022-04-14